On the human health benefits of microalgal phytohormones: An explorative in silico analysis - Angelo Del Mondo; Annamaria Vinaccia; Luigi Pistelli; Christophe Brunet; Clementina Sansone (Computational and Structural Biotechnology Journal, 2023)
Phytohormones represent a group of secondary metabolites with different chemical structures, in which belong auxins, cytokinins, gibberellins, or brassinosteroids. In higher plants, they cover active roles in growth or defense function, while their potential benefits for human health protection were noted for some phytohormones and little explored for many others. In this study, we developed a target fishing strategy on fifty-three selected naturally occurring phytohormones covering different families towards proteins involved in key cellular functions related to human metabolism and health protection/disease. This in silico analysis strategy aims to screen the potential human health-driven bioactivity of more than fifty phytohormones through the analysis of their interactions with specific targets. From this analysis, twenty-eight human targets were recovered. Some targets e.g., the proteins mitochondrial glutamate dehydrogenase (GLUD1) or nerve growth factor (NGF) bound many phytohormones, highlighting their involvement in amino acid metabolism and/or in the maintenance or survival of neurons. Conversely, some phytohormones specifically interacted with some proteins, e.g., SPRY domain-containing SOCS box protein 2 (SPSB2) or Inosine-5′-monophosphate dehydrogenase 1 (IMPDH1), both involved in human immune response. They were then investigated with a molecular docking analysis approach. Our bioprospecting study indicated that many phytohormones may endow human health benefits, with potential functional role in multiple cellular processes including immune response and cell cycle progression.